Locus geometricus - Céline Trautmann-Waller (Recherches Germaniques)
In Pierre Bourdieu’s 1967 Postscript to his translation of Erwin Panofsky’s Gothic Architecture and scholasticism, in which he quotes mostly theoreticians of art, culture and society from Germany and Austria, the expression “lieu géométrique” (in English texts locus geometricus) points to methodological and theoretical questions about the relation between the individual and the collective. From his first book publication in Germany (Zur Soziologie der symbolischen Formen, 1970) to the Outline of a Theory of Practice (1972, Engl. 1977), this expression articulated questions related to habitus, categories of perception and thinking, figuration, statistics and field theory. To analyze the link with Bourdieu’s critique of naturalization, situated in a tension between German philosophy and French sociology, this article enlarges the perspective by including the impact of the war and of his fieldwork in Algeria on Bourdieu’s thinking and his direct or indirect relation to the United States.